From ecological trade-offs to resilience: insights from exploited marine ecosystems. Issue 13 (February 2019) - Libralato, Simone; Agnetta, Davide
Abstract: Ecological trade-offs due to different perturbations are here quantified by comparing direct impacts and net effects using fishing pressures on marine ecosystems as controlled perturbations. Results highlight that trade-offs emerge in majority of cases when evaluated through multispecies models and are independent from model complexity. Trade-offs showed a dome-shaped relationship with direct impact, thus supporting the theory of positive effects of intermediate levels of disturbance. Moreover, trade-off intensity resulted to be related to the capability of the system to react to perturbation, that is, to ecosystem resilience. Overall, the work shows the benefit of complex system analysis that permits the emerging ecological trade-offs which are neglected in simpler single species analyses. Graphical abstract: Image 1 Highlights: A set of food web models are analyzed to quantify ecological trade-offs due to perturbations. Using fishing fleets as controlled perturbation experiments, trade-offs are emerging. Trade-offs showed a dome-shaped relation with direct impact, supporting the theory of intermediate disturbance. Magnitude of trade-offs depends on the level of integrity of the ecosystem, that is, its level of resilience.